1996
DOI: 10.1161/01.str.27.3.393
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Occlusive Lesions of Carotid and Intracranial Arteries in Japanese Patients With Ischemic Heart Disease

Abstract: Our data suggest that asymptomatic occlusive lesions in the carotid and intracranial arteries are fairly common in Japanese patients with IHD, although the degree of stenosis is relatively mild. Coexistence of carotid atherosclerosis should be suspected in IHD patients with severe coronary atherosclerosis, and the possibility of atherosclerosis in the intracranial arteries should be considered in aged IHD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 28 publications
4
59
1
2
Order By: Relevance
“…23 CIMT and presence of carotid plaque were not significantly related to LAICOD after adjusting for age and other confounding factors in our study, which further supported the existence of pathologic and pathophysiologic differences in atherogenesis of intra-and extracranial arteries. Some Asian studies [24][25][26] found that process of extracranial atherosclerosis might be more resembling to that of coronary atherosclerosis but not intracranial arterial atherosclerosis. For instance, Korean studies demonstrated that the correlation between coronary atherosclerosis and extracranial atherosclerosis was stronger than that of coronary atherosclerosis and intracranial atherosclerosis, independent of classic risk factors.…”
Section: Downloaded Frommentioning
confidence: 99%
“…23 CIMT and presence of carotid plaque were not significantly related to LAICOD after adjusting for age and other confounding factors in our study, which further supported the existence of pathologic and pathophysiologic differences in atherogenesis of intra-and extracranial arteries. Some Asian studies [24][25][26] found that process of extracranial atherosclerosis might be more resembling to that of coronary atherosclerosis but not intracranial arterial atherosclerosis. For instance, Korean studies demonstrated that the correlation between coronary atherosclerosis and extracranial atherosclerosis was stronger than that of coronary atherosclerosis and intracranial atherosclerosis, independent of classic risk factors.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Among patients who had undergone selective coronary angiography under diagnosis of ischemic heart disease, 22.4% had stenosis of more than 25% in the extracranial carotid arteries. 8) Among patients who underwent coronary artery bypass grafting, 4.1% had asymptomatic total occlusion of a carotid artery. 7) Annual cardiac event rate was 8.3% and mortality was 6.5% in patients with asymptomatic carotid artery stenosis of greater than 75%.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 40% of intracranial artery stenoses are located in the MCA. 8) Therefore, progression of occlusive diseases in the intracranial as well as the extracranial arteries is associated with increased risk of cardiac vascular events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ir vainikinių arterijų ateroskleroziniai pažeidimai koreliavo tarpusavyje. Tyrimas parodė, jog japonams, segantiems KŠL, gana dažnai nustatomi besimptomiai miego ir intrakranijinių arterijų stenoziniai pažeidimai, tačiau stenozės laipsnis yra gana mažas [11]. Korėjoje atliktame tyrime nustatyta, kad pacientai, turintys koronarinių arterijų stenozę bei KŠL, dažniau nei nesergantieji patirdavo intrakranijinių arterijų stenozės sukeltą GSI (61,1 proc.)…”
Section: Koronarine šIrdiesunclassified